Immunotherapy with CpG‐ODN in neoplastic meningitis: A phase I trial. Issue 9 (29th July 2015) - Ursu, Renata; Taillibert, Sophie; Banissi, Claire; Vicaut, Eric; Bailon, Olivier; Le Rhun, Emilie; Guillamo, Jean‐Sebastien; Psimaras, Dimitri; Tibi, Annick; Sacko, Adama; Marantidou, Athina; Belin, Catherine; et al.
<x xml:space="preserve">Abstract</x> TLR‐9 agonists are immunostimulating agents that have antitumor effects in animal models. A phase I trial was conducted to define the safety profile of subcutaneous injections, combined with intrathecally administration of CpG‐28, a TRL 9 agonist, in patients with neoplastic meningitis (NM). Cohorts of 3–6 patients with NM were treated for 5 weeks with escalating doses of CpG‐28. The primary endpoint was tolerance. Secondary endpoints were progression free survival (PFS) and overall survival (OS). Twenty‐nine patients were treated with CpG‐28. The primary cancers were malignant glioma, lung carcinoma, breast cancer, melanoma or melanocytoma, ependymoma, and colorectal cancer. The median age was 56 years and median Karnovsky Performance status (KPS) was 70%. The treatment was well tolerated. Adverse effects that were possibly or probably related to the studied drug were grade 2 lymphopenia, anemia and neutropenia, local erythema at injection sites, fever and seizure. There were five serious adverse events: two confusions, two infections of ventricular devices and one grade 4 thrombopenia and neutropenia. The median PFS was 7 weeks and median OS was 15 weeks. Interestingly, the median survival was slightly (but not significantly) higher in the eight patients who were concomitantly treated with bevacizumab (19 weeks vs 15 weeks; P = 0.11). CpG‐28 was well tolerated at doses up to 0.3 mg/kg subcutaneously and 18 mg intrathecally. Additional trials are warranted.